Ecological and Cost Advantage from the Implementation of Flight Simulation Training Devices for Pilot Training - Marta Maciejewska; Paula Kurzawska-Pietrowicz; Marta Galant-Gołębiewska; Michał Gołębiewski; Remigiusz Jasiński (Applied Sciences, 2024)
The paper discusses a case study of obtaining an airline pilot license in integrated training—the so-called “from zero to Airline Transport Pilot License”. The environmental implications of simulator-based training were examined across multiple dimensions. Key areas of research include the reduction of harmful exhaust gases pollution associated with traditional flight training activities. Based on our analysis, it can be stated that increasing the use of Flight Simulation Training Devices in pilot training should be significant consideration. This approach brings many benefits, especially ecological ones. Changing the training program and increasing the use of flight simulators can result in a reduction of CO2 emissions by up to 70%. Based on country specific electricity factors, CO2 emissions during flight training in each EU country were calculated. Using Levelized Cost of Electricity average value to calculate training costs in EU countries depends on the mix of energy sources (wind, photovoltaics, carbon and gas). The findings highlight the significant ecological advantages of simulator-based training methods in mitigating the environmental footprint of aviation operations. By seeking to minimize environmental disruption and increase training efficiency, the adoption of simulators is a sustainable approach to pilot training that is consistent with global efforts to mitigate climate change and protect natural ecosystems.